Dagomea Mieszko - Banasik, Wojciech (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
The paper attempts to solve the ‘perennial’ problem of Polish historiography and linguistics: the etymology of the mysterious personal names of the first historical Polish ruler – Dagome and Mieszko. The former is encountered only in the 11th-century digest known as Dagome Iudex. This is the Slavic name Drogomir distorted by German spelling and phonetics, as well as mistakes by scribes. It provides grounds for explaining the etymology of the latter name – commonly used with reference to the ruler. The name Mieszko is an exceptional diminutive; it derives from the second segment of the name Drogomir – Mir+jь+ko. The linguistic processes taking place in the Polish language at that time induced phonetic changes in the name and also led to its latter segment function as a separate name whose meaning became obsolete.